Between global aspirations and local identity: How cultural drivers and social referents shape Gen Z’s travel intentions in Saudi Arabia - Ahmed, Hebatallah; Fayyad, Sameh; Abdelghani, Abdelrahman (Research Journal in Advanced Humanities, 2025)
Saudi Arabia’s Vision 2030 seeks to diversify the economy through sustainable tourism that balances global aspirations with local identity. This study examines how cultural drivers and social referents shape Generation Z’s travel intentions in Saudi Arabia, aligning with SDG 3 (Good Health and Well-Being), SDG 8 (Decent Work and Economic Growth), and SDG 11 (Sustainable Cities and Communities). A quantitative survey of 447 Saudi Gen Z respondents (aged 18–28) employed validated five-item scales for cultural drivers, social referents, domestic destination attractiveness, international destination appeal, and travel intention. Data were analyzed using PLS-SEM to test direct and moderating effects. Results: Both cultural drivers (β = 0.211, p < .001) and social referents (β = 0.358, p < .001) significantly influenced travel intentions. Domestic destination attractiveness positively moderated these relationships (β_CD×DDA = 0.142, p = .011; β_SR×DDA = 0.134, p = .017), whereas international destination appeal did not. Findings highlight that enhancing local cultural assets and peer-driven marketing can foster sustainable tourism development (SDG 12) while supporting Saudi priorities in environmental sustainability, human capital, and future economies. By integrating social identity and cultural consumption theories, the study provides actionable insights for policymakers and industry stakeholders to advance heritage tourism, renewable energy investments in tourism infrastructure, and community well-being initiatives.